First‐principle calculations, crystal growth, and broadband near‐infrared luminescence of Nd:Y2Mg3(SiO4)3 single crystal - Li, Lin; Zhang, Peixiong; Li, Zhen; Chen, Zhenqiang (Journal of the American Ceramic Society, 2025)
This study successfully grew Y2Mg3(SiO4)3 (YMS) single crystals doped with Nd3+ ions via laser heated pedestal growth method for the first time. Based on first‐principle calculations, the structural relaxation, energy band structure, density of states, and optical properties of YMS and Nd:YMS crystals with multiple disordered structures were calculated for the first time. The refractive index of the YMS crystal was obtained to be 1.83. The optical properties including absorption spectra, near‐infrared (NIR) luminescence spectra, and fluorescence lifetime at 1080 nm (Nd3+: 4F3/2→4I11/2) were characterized and analyzed based on the grown Nd:YMS single crystal. The crystal was found to have an ultra‐wide half‐height width (46.99 nm) of emission cross‐section, and a fluorescence lifetime of 220.38 µs, making it a luminescence material with excellent comprehensive performance. In the first growth of a novel single crystal, Nd:Y2Mg3(SiO4)3, a broad FWHM of absorption cross‐section at 807 nm (31.62 nm) and an ultra‐broad FWHM emission cross‐section at 1.08 nm (46.99 nm) have been obtained for tunable and ultrafast lasers applications. The geometry, electronic, and optical properties were further explored via first‐principle calculations.